Clinical role of CD274 (PD-L1) and CD3+ lymphocytes in predicting high risk in advanced colorectal cancer patients receiving neoadjuvant chemotherapy - Benek, Suat; Zengin, Mehmet (Polish Journal of Pathology, 2023)
In cancer research, the mechanism underlying the immune response to a tumour has been of great interest. In this study, we investigated the role of CD274 (programmed cell death-ligand 1 – PD-L1) and CD3+ tumour-infiltrating lymphocytes (TILs) in the prognosis of advanced colorectal cancer (CRC) patients treated with neoadjuvant chemotherapy. We retrospectively examined primary tumour specimens from stage III/IV CRC patients operated on between 2008 and 2018. We found a significant association between these biomarkers and pT stage (PD-L1, p = 0.020; CD3+TILs, p = 0.025), tumour grade (PD-L1, p = 0.005; CD3+TILs, p = 0.004), positive surgical margin (PD-L1, p = 0.001; CD3+TILs, p = 0.001), MSI (PD-L1, p < 0.001; CD3+TILs, p < 0.001), etc. We also discovered that these biomarkers are independent risk factors for MSI (PD-L1, OR = 1.84 [1.27–4.02], p = 0.003; CD3+TILs, OR = 1.92 [1.31–4.35], p = 0.008). Univariate analysis results revealed that patients with high PD-L1, low CD3+TIL, and both showed poor relapse-free survival (RFS) and poor overall survival (OS) (PD-L1: RFS, p = 0.008 and OS, p = 0.001; CD3+TILs: RFS, p = 0.003 and OS, p = 0.005; PD-L1 and CD3+TILs: RFS, p < 0.001 and OS, p < 0.001). The results of the multivariate analysis showed that the combined use of high PD-L1 and low CD3+TILs was a better predictor of poor RFS and OS (PD-L1 and CD3+TILs: RFS, hazard ratio – HR, = 2.85 [95% CI: 1.36–3.84], p < 0.001); OS, HR = 2.74 [1.32–3.71], p < 0.001). We also found a high PD-L1 parameter as another independent overall and relapse-free survival parameter. Our findings suggest that a combination of high PD-L1 and low CD3+TIL can reliably predict poor survival in CRC patients receiving chemotherapy. Therefore, these biomarkers may be promising for the planning and execution of appropriate targeted therapies.